Spectral-Wise Method Derived by Optical Images For Phosphate Mineral Exploration In Mamuju, West Sulawesi, Indonesia - Kurniawan, Rajab; Saepuloh, Asep (Geological Agency, 2025)
Phosphates are predominantly used in the manufacture of fertilizers for crop nutrition and the production of animal feed supplements. Only 10 – 15 % of the world phosphate rock production has other uses, such as pharmaceuticals, ceramics, an important alternative source of rare earth elements (REE), and Lithium-Iron-Phosphate (LFP) batteries. In Indonesia, various types of rocks are composed of phosphate components, but rocks containing economic value are limited. They are generally found in sedimentary or biogenic phosphate deposits, whereas phosphate resources derived from igneous rocks are still undiscovered. Therefore, regionally accurate mapping using spectral-wise methods is proposed in this study. The five spectral references originated from phosphate minerals from the USGS spectral library were used: fluorapatite, chlorapatite, hydroxylapatite, monazite, and xenotime. The spectral-wise aims to identify anomalies of phosphate minerals based on the behaviour of spectral absorption at wavelength 2 µm. Their spectra showed a similar absorption pattern at a wavelength of 2 µm originating from orthophosphate (PO4). This spectral-wise formulation was then applied to detect the phosphate occurrences using the Landsat 9 image. According to the proposed method, three PO4 prospect zones could successfully be detected covering 2,604 Ha with P2O5 content reaching 1.14 ̶ 2.73 %. It has been verified that the proposed method has an accuracy of about 70 % compared to rock samples containing P2O5 at the field study.